2021
DOI: 10.1002/acr2.11273
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Dust Exposure During Military Service as a Predictor of Rheumatoid Arthritis and Other Autoimmune Conditions

Abstract: Objective. Rheumatoid arthritis (RA) and other autoimmune (AI) conditions are associated with inorganic dust exposure. Many military activities are likely to entail inorganic dust exposures. We wished to identify associations between prior military dust exposure and RA and other AI conditions.Methods. We studied persons from a roster of Army, Navy, Air Force, or Marine Corps personnel who had served in Operation Enduring Freedom and Operations Iraqi Freedom and New Dawn. We linked military occupational codes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…In summary, this analysis supports and amplifies our previous findings of a strong association between coal mining and other silica-exposing dust trades in Appalachia and RA, taking into account age, smoking and occupational ergonomic risks, the latter being largely overlooked as a cofactor in work-related RA. These findings add to a growing body of literature on increased risk of RA associated not only with silica but other exposures as well, across a range of vocational factors 20–27. In arthritis in general, but especially in RA, clinicians should consider occupational histories in the aetiology of disease, in both current and retired workers.…”
Section: Discussionmentioning
confidence: 64%
“…In summary, this analysis supports and amplifies our previous findings of a strong association between coal mining and other silica-exposing dust trades in Appalachia and RA, taking into account age, smoking and occupational ergonomic risks, the latter being largely overlooked as a cofactor in work-related RA. These findings add to a growing body of literature on increased risk of RA associated not only with silica but other exposures as well, across a range of vocational factors 20–27. In arthritis in general, but especially in RA, clinicians should consider occupational histories in the aetiology of disease, in both current and retired workers.…”
Section: Discussionmentioning
confidence: 64%
“…Adverse respiratory effects from deployed military base burn pits (devoted to open-air combustion of waste) are well documented, although no clear link with SLE was seen after up to 2.8 years of follow-up in a large US cohort, possibly due to power issues (the average follow-up was only 1.3 years) or outcome ascertainment error (since SLE was identified on the basis of electronic medical records and not otherwise clinically confirmed) [68,69]. Another recent study using a military job exposure matrix surprisingly reported an inverse association with inorganic dust exposure and SLE risk among veterans receiving care through the US Veteran's Affairs medical system [70]. Evidence for other respiratory exposures, such as organic dusts (i.e., molds, pollens, animal matter, grains, plant fibers, etc.)…”
Section: Respiratory Exposuresmentioning
confidence: 99%
“…2 Military inorganic dust exposure has also been associated with the development of RA compared to other occupations within the armed forces. 3 Prolonged exposure to the World Trade Center disaster site has also been associated with an increased rate of autoimmune disease, the most prevalent of which was RA. 4 Other occupations have demonstrated gender-specific associations with RA: bricklayers and concrete workers have an increased risk of RA among men, while nurses and Copyright © 2022 by the American Thoracic Society medical attendants have increased risk among women.…”
Section: To the Editormentioning
confidence: 99%
“…One telephone survey in an area with high mortality from coal workers’ pneumoconiosis found that residents with a history of coal mining exposure had more than threefold odds of reporting a diagnosis of RA, leading to a population attributable fraction of 33% of those studied ( 2 ). Military inorganic dust exposure has also been associated with the development of RA compared with other occupations within the armed forces ( 3 ). Prolonged exposure to the World Trade Center disaster site has also been associated with an increased rate of autoimmune disease, the most prevalent of which was RA ( 4 ).…”
mentioning
confidence: 99%